MODULATED STRUCTURES STABILIZED BY SPIN SOFTENING - AN EXPANSION IN INVERSE SPIN ANISOTROPY - Seno, F; Yeomans, J (1995)
We develop an analytic approach which allows us to study the behavior of spin models with competing interactions and p-fold spin anisotropy D in the limit where the pinning potential which results from D is large. This is an expansion in inverse spin anisotropy which must be carried out to all orders where necessary. Interesting behavior occurs near where the boundary between different ground states is infinitely degenerate for infinite D. Here as D decreases and the spins are allowed to soften, we are able to demonstrate the existence of several different behaviors ranging from a single first-order boundary to infinite series of commensurate phases. The method is illustrated by considering the soft chiral clock model and the soft clock model with first- and second-neighbor competing interactions. In the latter case the results are strongly dependent on the value of p. © 1995 The American Physical Society.